(untitled) (ENTHYMEMA, 2020)
In postcolonial literature, figures of aphasic or mute women often appear. These are characters who do not speak, by choice or by inhibition: women who do not have or have lost the use of the word; girls with almost autistic traits; disturbing, intriguing female figures who refuse to express themselves through language, all women who live the relationship with the outside world as violence. Precisely by reacting to this situation, the female characters of the most recent postcolonial novels begin to speak: first by babbling, like children who are trying out a new language, then putting together words, in the end whole sentences. And finally they come to tell us about themselves, to narrate their story, realizing that each person is his/her own story, and that the most subtle violence perpetrated on women is to silence them.